2022
DOI: 10.1038/s41598-022-09538-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined abiotic stresses on nutrient content of European wheat and implications for nutritional security under climate change

Abstract: Climate change is causing problems for agriculture, but the effect of combined abiotic stresses on crop nutritional quality is not clear. Here we studied the effect of 10 combinations of climatic conditions (temperature, CO2, O3 and drought) under controlled growth chamber conditions on the grain yield, protein, and mineral content of 3 wheat varieties. Results show that wheat plants under O3 exposure alone concentrated + 15 to + 31% more grain N, Fe, Mg, Mn P and Zn, reduced K by − 5%, and C did not change. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In line with the strong genetic and environmental trade‐off between grain yield and protein content (Galani et al, 2022 ; Scott et al, 2021 ), our results suggest a negative effect of increased temperatures throughout the growing season on protein content in the major wheat growing regions in the East of the UK. Indeed, our results showed that the land area with sufficiently high protein levels is likely to decrease to less than one eighth of the area in the current climate average.…”
Section: Discussionsupporting
confidence: 85%
“…In line with the strong genetic and environmental trade‐off between grain yield and protein content (Galani et al, 2022 ; Scott et al, 2021 ), our results suggest a negative effect of increased temperatures throughout the growing season on protein content in the major wheat growing regions in the East of the UK. Indeed, our results showed that the land area with sufficiently high protein levels is likely to decrease to less than one eighth of the area in the current climate average.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have reported a decline in seed protein content with increasing yield in soybean (Singh et al, 2016) and wheat (Fernando, Panozzo, Tausz, Norton, Neumann, et al, 2014;Galani et al, 2022). The path analysis approach allowed us to identify the yield-independent component of eCO 2 on protein content (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Keeping the above points in mind, beneficial symbiotic fungal endophytes working at a micro-ecosystem level forming rhizosphere offer an immense scope of research for CSA benefaction. Their non-pathogenic nature, universal occurrence, triggered nutrient uptake, mineral solubilization, phytoremediation, enhanced vegetative and reproductive growth, stress tolerance resulting in optimum to high yield, etc., make them suitable for organizing full-fledged scientific research and attention ( Galani et al, 2022 ). Fungal endophytes are reported to increase biomass and remove litter from the soil, increase mineral status and nutrient uptake which aids in achieving CSA concept indirectly ( Datta et al, 2017 ; Santamaria et al, 2017 ).…”
Section: Climate-smart Agriculture: Facts and Faithsmentioning
confidence: 99%
“…Endophytic fungi increase internal hyphal growth and colonization, carbon sequestration, biomass, and yield via increased photosynthesis and induced compositional changes in elevated CO 2 ( Galani et al, 2022 ). In this context, various researchers found symbiotic relationship beneficial as it escalates plant growth in crops viz.…”
Section: Fungal Endophytes For Abiotic Stress Managementmentioning
confidence: 99%
See 1 more Smart Citation